KETERAMPILAN PEMECAHAN MASALAH MELALUI PENERAPAN THE STRUCTURE OF THE OBSERVED LEARNING OUTCOME (SOLO) PADA PEMBELAJARAN FISIKA DIKELAS XI LINTAS MINAT FISIKA SMAN 12 PEKANBARU - Viva Satianingsih; Hendar Sudrajad; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to describe how the students' problem solving skills through the implementation of the model SOLO (the structure of the observed learning outcomes) in physics learning in class XI traffic Interest Physics SMAN 12 Pekanbaru. This research was conducted at SMAN 12 Pekanbaru in November until January 2016 using One shot chase study design. Subjects consisted of 38 students consisting of 15 male students and 23 female students. Data was collected by giving the test description about 5 question in the end of the study with the implementation of SOLO. From the results of the research showed that the student's skills in solving problems is very low category with an average score of 63. The skills of students at the stage of understanding the problem is the very high category with an average score of 90. The skills of students in the planning stages of problem solving are the very low category with an average score of 56. The skills of students at the stage of implementing the settlement of the problem is the very low category with an average score of 65. And the skills of students on stage to re-examine the solution in the category are very low with an average score at 41. It can be concluded that the learning model SOLO ineffective to train problem-solving skills in learning physics class XI traffic interest Physics SMAN 12 Pekanbaru.Key Words : Physics, Problem Solving Skills, SOLO Model